Osteocyte density in aging subjects is enhanced in bone adjacent to remodeling haversian systems. - Power, J; Loveridge, N; Rushton, N; Parker, M; Reeve, J (2002)
The osteocyte is a candidate regulatory cell for bone remodeling. Previously, we demonstrated that there is a substantial (approximately 50%) loss of osteocytes from their lacunae in the cortex of the elderly femoral neck. Higher occupancy was evident in tissue exhibiting high remodeling and high porosity. The present study examines the distribution of osteocytes within individual osteonal systems at differing stages of the remodeling cycle. In 22 subjects, lacunar density, osteocyte density, and their quotient, the percent lacunar occupancy, was assessed up to a distance of 65 microm from the canal surface in six quiescent, resorbing, and forming osteons. In both forming (p = 0.024) and resorbing (p = 0.034) osteons, osteocyte densities were significantly higher in cases of hip fracture than controls. However, there were no significant between-group differences in lacunar occupancy. In both cases and controls, osteocyte density (p < 0.0001; mean difference +/-SEM: 157 +/- 34/mm2) and lacunar occupancy (p = 0.025; mean difference: 8.1 +/- 3.4%) were shown to be significantly higher in forming compared with quiescent osteons. Interestingly, resorbing systems also exhibited significantly elevated osteocyte density in both the fracture and the control group combined (mean difference 76 +/- 23/mm2; p = 0.003). Lacunar occupancy was also greater in resorbing compared with quiescent osteons (both groups combined: p = 0.022; mean difference: 5.7 +/- 2.3%). Elevated osteocyte density and lacunar occupancy in forming compared with quiescent systems was expected because of the likely effects of aging on quiescent osteons. However, the higher levels of these parameters in resorbing compared with quiescent systems was the opposite of what we expected and suggests that, in addition to their postulated mechanosensory role in the suppression of remodeling and bone loss, osteocytes might also contribute to processes initiating or maintaining bone resorption.